International Obligations, State Responsibility and Judicial Review Under the OECD Guidelines for Multinational Enterprises Regime. Issue 78 (28th February 2014) - Robinson, Scott
The OECD Guidelines for Multinational Enterprises were viewed at their genesis as political commitments not legally binding on states and only voluntary for corporations. Due to the OECD Council Decision on the Guidelines for Multinational Enterprises in 2000/2011, however, OECD Member States are compelled to implement this regime by the establishment and operation of a National Contact Point (NCP) as a state-based, non-judicial, dispute resolution mechanism to handle complaints concerning corporations operating from or within their respective jurisdictions. This paper does not analyse weaknesses in the often-troubled NCP system nor does it propose reforms. Rather, it examines the current system from the legal perspective of OECD Member States and explores the relatively ignored extent of their obligations under it. This paper posits that on account of the Council Decision, treaty-derived, international obligations are in fact imposed on OECD Member States under the NCP system and that NCP maladministration can lead to state responsibility at international law. In any event, however, it seems clear that there does not exist any review mechanism—domestically or internationally—capable of attributing internationally wrongful conduct to an OECD Member State on account of its NCP.